Topographical-anatomical and clinical aspects of the assessment of Merzlikin-Paramonova's approach to liver surgeries - N. V. Merzlikin; L. Y. Petrov; V. F. Tskhai; A. A. Sotnikov; L. M. Paramonova; T. A. Noroeva; M. E. Maryina; M. Y. Grishchenko; A. P. Sarueva; V. G. Navasardyan (Сибирский онкологический журнал)
The purpose of the study was to assess results of Merzlikin-Paramonova's approach in liver surgeries.Material and Methods. The topographical-anatomical and spatial relationships were studied on 20 corpses, taking into account assessment criteria according to A.Yu. Sozon-Yaroshevich. In clinical settings, Merzlikin-Paramonova's approach was applied in the treatment of 81 patients with hepatic diseases (cancer, hemangioma, alveococcosis), who underwent radical and palliative surgeries. Short-and long-term treatment outcomes during a 5 year follow-up were analyzed. Merzlikin-Paramonova's approach provided a sufficient overview of the liver, easy manipulation in the area of large bile ducts and blood vessels, as well as the ability to perform lymphodissection and combined operations.Results. The Merzlikin-Paramonova's approach to liver surgeries has significant advantages over traditional surgical approaches, providing a good overview for revision of both primary and recurrent liver lesions. This surgical approach allowed the number of postoperative complications to be reduced due to less wound tension, rapid relief of pain and reduction in intra-abdominal hypertension, thus shortening the treatment time for patients. In the long-term postoperative period, the incidence of postoperative hernias decreased due to less damage to the nerve terminals of the anterior abdominal wall.Conclusion. Merzlikin-Paramonova's approach is slightly traumatic due to innervation and muscle structure of the abdominal wall, is more physiological for the patient, and has a low rate of complications. This approach provides a good access to the organ requiring surgery and is able to perform radical cytoreductive surgeries. Merzlikin-Paramonova's approach to liver surgeries can be recommended for active implementation in clinical practice.